Evaluation of the Effect of Repetitive Transcranial Magnetic Stimulation of Motor Cortex on Failed Back Surgery Syndrome Pain Control in the Short Term - Soltani, Ahmad; Ghavipisheh, Mahsa; Ardakani, Ramin Manouchehri; Ahrari, Iman; Salehi, Sina; Farrokhi, Majid Reza (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background This study aimed to evaluate the short-term efficacy of repetitive transcranial magnetic stimulation (rTMS) on the treatment of failed back surgery syndrome (FBSS).Methods In this prospective clinical trial study, 13 patients with FBSS were selected to undergo rTMS, including 5 sessions of stimulation of the primary motor cortex of 90 trains with a frequency of 10 Hz for 2 seconds and an intertrain interval of 20 seconds with a total pulse rate of 1800 per session. The time of each session was 30 minutes with an intensity of 80% of the motor threshold. The severity of pain before and after the intervention was measured by the short-form McGill Pain Questionnaire and visual analog scale (VAS).Results The mean of pain severity was 26.54 ± 6.78 and 14.92 ± 10.1 before and after rTMS, respectively. The severity of pain was significantly decreased after the intervention (p = 0.001). According to the McGill Pain Questionnaire, the severity of pain in the patients was decreased by 44.09 ± 27.32. The mean of the severity of pain according to VAS was 77.31 ± 16.66 before rTMS and 53.46 ± 22.49 after rTMS, which showed that pain intensity was significantly decreased after the intervention (p = 0.006).Conclusions The use of rTMS of the primary motor cortex in patients who have undergone lumbosacral spine surgery and suffer from pain related to FBSS is associated with a significant reduction in the severity of pain. Because rTMS is a noninvasive treatment method, it can be used as a suitable treatment in these patients.
Keywords: lumbosacral spine surgery; failed back surgery syndrome; repetitive transcranial magnetic stimulation